Sundanese Printed Kitābs in Egypt: Notes on the contribution of Mukhtār ‘Aṭārid al-Bughūrī’s works - Rohmana, Jajang A (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2022)
Mukhtār ‘Aṭārid al-Bughūrī (1862–1930) is one of Sundanese ulamas from Bogor who became a religious teacher or sheikh in Mecca. His students were many ulamas from the Middle East and Southeast Asia. However, compared to the other works of Sundanese ulamas, Mukhtār ‘Aṭārid’s works are less known despite his significant contribution. He is one of Sundanese ulamas who published printed Islamic books or kitābs in Sundanese with pegon script in Egypt. To further explore about Mukhtār ‘Aṭārid al-Bughūrī’s works, this study focuses on three Sundanese printed kitābs of his: Ieu Kitāb ‘Aqā’id, Kifāyat al-Mubtadi’īn, and Hidāyat al-Mubtadi’īn. These kitābs were learned by beginner students from West Java taught by Mukhtār ‘Aṭārid in Mecca. This study confirms that the Islamic learning transmission between Mecca and Southeast Asia in the early twentieth century emerged a diversity of languages in the teaching the kitābs. The sheikh responded to the increasing diversity of the East Indies students in Mecca through various printed kitābs with trans- regional languages amidst the growing printing business in the early twentieth century. It was an effort to facilitate Islamic teaching and learning traditions at the time. In addition, these kitābs also demonstrate Mukhtār ‘Aṭārid’s efforts in maintaining Sunnī traditionalist doctrines amid the Salafi/Wahhabi ideology which became the official religious teachings of the Saudi government in Mecca.